2006
DOI: 10.1039/b601306f
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic oxidation of ammonia on Pt(111) and Pt(100) surfaces

Abstract: The electrocatalytic oxidation of ammonia on Pt(111) and Pt(100) has been studied using voltammetry, chronoamperometry, and in situ infrared spectroscopy. The oxidative adsorption of ammonia results in the formation of NH(x) (x = 0-2) adsorbates. On Pt(111), ammonia oxidation occurs in the double-layer region and results in the formation of NH and, possibly, N adsorbates. The experimental current transients show a hyperbolic decay (t(-1)), which indicates strong lateral (repulsive) interactions between the (re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
178
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(187 citation statements)
references
References 47 publications
8
178
1
Order By: Relevance
“…Vidal-Iglesias et al [77] also found the formation of N 2 H 4 during the ammonia electro-oxidation process by SERS. However, Pt (111) surface gives a deeper dehydrogenation of NH 3,ads to strongly adsorbed NH and N fragments, which fails to form N 2 at an appreciable rate [74]. Density functional theory (DFT) calculations also support that the adsorption of the NH 2 fragment is more favorable on Pt (100) than on Pt (111) [78].…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Vidal-Iglesias et al [77] also found the formation of N 2 H 4 during the ammonia electro-oxidation process by SERS. However, Pt (111) surface gives a deeper dehydrogenation of NH 3,ads to strongly adsorbed NH and N fragments, which fails to form N 2 at an appreciable rate [74]. Density functional theory (DFT) calculations also support that the adsorption of the NH 2 fragment is more favorable on Pt (100) than on Pt (111) [78].…”
Section: Resultsmentioning
confidence: 69%
“…The partially dehydrogenated NH 2,ads species are active intermediates to give the final product of N 2 while the fully dehydrogenated products (i.e., N ads ) poison the Pt surface. It has been widely reported that the electrocatalytic activity of the Pt (100) sites for ammonia electro-oxidation is significantly high [21,22,24,38,44,74]. This surface-structure sensitivity has been well demonstrated on both model Pt single crystal surfaces and Pt NPs with (100) preferential orientation prepared by different methods [21,22,24,38,75].…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…7). This peak has been previously ascribed to the oxidative (reductive) adsorption (desorption) of ammonia on Pt (100) [69]. All these findings indicate that the resulting reactivity towards ammonia oxidation will depend of different factors including (i) active surface area, (ii) metal loading and (ii) thickness of the catalytic layer.…”
Section: Ammonia Electrooxidationmentioning
confidence: 80%
“…The difference between Pt(100) and Pt(111) and the different stability of NH 2 compared with NH and N are in very good agreement with the recent results by Rosca and Koper. 35 These authors have related the relatively high electrocatalytic activity of Pt(100) for ammonia oxidation to dinitrogen to its ability to stabilize the NH 2 adsorbate. Figure 4 presents the geometry of initial, transition, and final states corresponding to the most stable situation on the 2 × 2 unit cell for all of the elemental dehydrogenation reactions.…”
Section: ) and Height From The Surface Layer (Z) (Distances In Angstmentioning
confidence: 99%